Modernisasi Pendidikan Islam di Mesir, Malaysia dan Indonesia - Takwil, Moh. (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2023)
Comparative studies of Islamic education in Muslim countries are important to be carried out, both from efforts to modernize education and to renewing policies. By doing this comparison, it can become a reference and choice of a suitable educational model that will be applied to Islamic educational institutions. In this journal discusses the comparative modernization of Islamic education in Egypt, Malaysia and Indonesia using content analysis. The results of the study found that there are similarities in the renewal of Islamic education from the three countries (Egypt, Malaysia and Indonesia), namely on two sides, first from the institutional side. That Egypt, Malaysia and Indonesia are undergoing a renewal of traditional patterns such as kuttab, mosques, surau to the modern institutional model that uses classical. Second, from the curriculum applied is the integration of general science with religion. Religious subjects are applied in public schools, also general subjects are applied in religious schools. However, there are differences, among others, Egypt is strongly influenced by the enthusiasm of student learning to the west, while Malaysia and Indonesia are actually influenced by the existence of Indonesian religious scholars who study in the Middle East.